Complete mitogenome of two moray eels of Gymnothorax formosus and Scuticaria tigrina (Anguilliformes: Muraenidae). (3rd July 2016) - Loh, Kar-Hoe; Shao, Kwang-Tsao; Chen, Ching-Hung; Chen, Hong-Ming; Then, Amy Yee-Hui; Loo, Poh-Leong; Lim, Phaik-Eem; Chong, Ving-Ching; Shen, Kang-Ning; Hsiao, Chung-Der
Abstract: In this study, the complete mitogenome sequence of two moray eels of Gymnothorax formosus and Scuticaria tigrina (Anguilliformes: Muraenidae) has been sequenced by the next-generation sequencing method. The assembled mitogenome, with the length of 16, 558 bp for G. formosus and 16, 521 bp for S. tigrina, shows 78% identity to each other. Both mitogenomes follow the typical vertebrate arrangement, including 13 protein coding genes, 22 transfer RNAs, two ribosomal RNAs genes, and a non-coding control region of D-loop. The length of D-loop is 927 bp ( G. formosus ) and 850 bp ( S. tigrina ), which is located between tRNA-Pro and tRNA-Phe. The overall GC content is 45.5% for G. formosus and 47.9% for S. tigrina . Complete mitogenomes of G. formosus and S. tigrina provide essential and important DNA molecular data for further phylogenetic and evolutionary analysis for moray eel.